Quantum correlations between single telecom photons and a multimode on-demand solid-state quantum memory - Seri, A; Lenhard, A; Rieländer, D; Gündoğan, M; Ledingham, P; Mazzera, M; De Riedmatten, H (American Physical Society, 2017)
Quantum correlations between long-lived quantum memories and telecom photons that can propagate with low loss in optical fibers are an essential resource for the realization of large-scale quantum information networks. Significant progress has been realized in this direction with atomic and solid-state systems. Here, we demonstrate quantum correlations between a telecom photon and a multimode ondemand solid state quantum memory. This is achieved by mapping a correlated single photon onto a spin collective excitation in a Pr3+:Y2SiO5 crystal for a controllable time. The stored single photons are generated by cavity-enhanced spontaneous parametric down-conversion and heralded by their partner photons at telecom wavelength. These results represent the first demonstration of a multimode on-demand solid state quantum memory for external quantum states of light. They provide an important resource for quantum repeaters and pave the way for the implementation of quantum information networks with distant solid state quantum nodes.